Annual Plan 2005-2006 (Volume-II) National Capital Territory of Delhi - Planning Commission (Planning Commission, 2005)
Govt, has opened, upgraded and bifurcated number of schools during 9th Five Year Plan to provide easy access to students wherever it was necessary. The position of schools opened, upgraded or bifurcated during 9th Five Year Plan and Annual Plan 2002-03 and 2003-04 of 10th Five Year Plan is as under.
Planning Department, Government of National Capital Territory of Delhi